An Unusual Origin of Fetal Lymphangioma Filling Right Axilla - Ersoy, Ali Ozgur (J Clin Diagn Res, 2016)
Fetal lymphangioma is a hamartomatous congenital anomaly of the lymphatic system, which is embracing the fetal skin (sometimes mucous membranes) and the subcutaneous tissue. The general consensus is that it occurs as a result of failure in lymphatic drainage. A 36-year-old pregnant woman was referred to our perinatology clinic at 22 weeks’ gestation, because of a fetal right-sided axillary mass revealed by ultrasonography. The mass measuring 5x7x7cm in three dimensions had a multilocular structure without colour Doppler flow and well-circumscribed borders. Amniocentesis revealed a normal constitutional karyotyping. Lymphangioma was considered as prediagnosis. A healthy female baby weighing 3470 grams was delivered at term. Neonatal examination and the postnatal MRI confirmed the diagnosis. The baby is still on follow-up with the medical treatment of Sirolimus an anti-proliferative drug, and the mass got smaller significantly in 8 months after delivery.